Surgical treatment of nasal non-melanoma skin cancer in elderly patients using dermal substitute. (1st December 2016) - Dessy, Luca Andrea; Marcasciano, Marco; Fanelli, Benedetta; Mazzocchi, Marco; Ribuffo, Diego
Abstract: Conclusions: The nose is often involved by non-melanoma skin cancer (NMSC) and the increase in the incidence of such tumors, the morbidity and treatment-related costs represent a significant burden to healthcare systems. A bioresorbable dermal substitute (Hyalomatrix ® ) has been used for immediate dermal coverage and nose restoration after excision of infiltrating nasal NMSCs in elderly ASA III patients. Further studies on dermal substitutes are needed to improve benefit to patients. Objective: Surgical treatment of nasal non-melanoma skin cancer (NMSC) in elderly patients. Materials and methods: Ten elderly ASA III patients with nasal defects after resection of infiltrating NMSC were reconstructed in a two-stage strategy. The surgical protocol targeted an initial wide tumor excision and apposition of a dermal induction template (Hyalomatrix ® ) and successive full thickness skin autograft. Results were documented by photography, visual analog scale for patient satisfaction, and Vancouver scar scale for evaluation of final graft characteristics. Results: All patients were tumor-free during the 2 years follow-up. The procedure achieved acceptable nose reshaping and graft scarring evolution. Patient satisfaction was good-to-high.